Intense training influences musculoskeletal characteristics of prepubertal female gymnasts - Petersen, S. R.; Gaul, C. A.; Stanton, M. M.
Objective The objective of this research was to investigate the effects of chronic, intense physical training on the musculoskeletal system in prepubertal females. The findings from this study may provide insight into the alterations in the structure and function of muscle and bone tissue in response to heavy training in prepubertal females. Results The groups did not differ in height or weight but there was a significant difference in the sum of the skinfold thicknesses (TG: 31.5 mm vs RG: 55.6 mm). There were no stastically significant differences in either absolute GCSA or TCSA. However, when GCSA was corrected for body mass, the TG values were significantly greater (p<.05) than for RG. Similar results were observed when TCSA was corrected for body size (p<.05). When supramximal exercise work loads were expressed relative to GCSA, the TG values were higher than those of the RG (p<.05). Conclusions These results demonstrate the significant influence of physical training on both muscle and bone development in prepubertal females. While training was not controlled in this cross sectional study, an extensive training and competitive history clearly distinquished the TG from the RG. The larger TCSA provides evidence for training induced osteogenic (bone development) activity. Further, the higher work outputs per GCSA in the trained subjects suggests greater neuromuscular control compared to the less well trained females.